2019
DOI: 10.1175/jcli-d-18-0021.1
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of Tibetan Plateau Vortices in Reanalysis Data and a High-Resolution Global Climate Model

Abstract: The Tibetan Plateau (TP) and surrounding high mountains constitute an important forcing of the atmospheric circulation due to their height and extent, and thereby impact weather and climate in downstream regions of East Asia. Mesoscale Tibetan Plateau vortices (TPVs) are one of the major precipitation-producing systems on the TP. A fraction of TPVs move off the TP to the east and can trigger extreme precipitation in parts of China, such as the Sichuan province and the Yangtze River valley, which can result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…Hunt et al (2019) showed that historical simulations in CMIP5 GCMs generally represented the structure well, while overestimating the frequency and intensity. Ridley et al (2013) used a weather regime clustering technique with a regional climate model to argue that western disturbances and associated snowfall may increase in the future; however, their result was sensitive to the GCM used to force the boundaries of their RCM, their domain included the Tibetan Plateau and they did not separate the potential effects of Tibetan Plateau vortices (e.g., Curio et al 2019;Hunt et al 2018a) from WDs. In a more general way, Chang et al (2012) used 24-h bandpassfiltered meridional wind variance as a proxy for synoptic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Hunt et al (2019) showed that historical simulations in CMIP5 GCMs generally represented the structure well, while overestimating the frequency and intensity. Ridley et al (2013) used a weather regime clustering technique with a regional climate model to argue that western disturbances and associated snowfall may increase in the future; however, their result was sensitive to the GCM used to force the boundaries of their RCM, their domain included the Tibetan Plateau and they did not separate the potential effects of Tibetan Plateau vortices (e.g., Curio et al 2019;Hunt et al 2018a) from WDs. In a more general way, Chang et al (2012) used 24-h bandpassfiltered meridional wind variance as a proxy for synoptic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further examination based on higher resolution data is needed. In addition, the manual tracking of TPVs in this work is subjective, thus, the objective tracking method (Curio et al, 2018;Curio et al, 2019) should be utilized in future work, which is beneficial for the climatological study of TPVs. Moreover, although the dynamic and thermodynamic effects on EPDs are revealed in this work, questions remain regarding their relative roles and the different mechanisms involved before, during, and after moving off the Tibetan Plateau.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In fact, the TPV is a mesoscale weather system (Luo, 1994;Lin, 2015) with an average radius of less than 500 km, which is unlikely to affect such a wide geographical range, and thus it will greatly overestimate the precipitation related to TPVs. In recent studies, Curio et al (2019) use a geodesic radius of 3 around the TPV centre. Their scheme is similar to the method of Hawcroft et al (2012) that relates the precipitation with extratropical cyclones, although the cap scale used by Hawcroft et al (2012) is significantly larger (10 /12 in winter/summer) due to the larger size of the systems.…”
Section: Tpv Tracking and Its Associated Precipitationmentioning
confidence: 99%